2017
DOI: 10.1002/hed.25004
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of tonsil‐derived mesenchymal stem cells on osteoradionecrosis in a rat model

Abstract: A single 20-Gy dose of irradiation combined with tooth extraction successfully generated ORN in the rat model. The tonsil-derived MSCs can be effective for bone regeneration in ORN, particularly when applied immediately after dentoalveolar trauma or surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Recently, palatine tonsil tissue was also identified as a source of MSCs and tonsil-derived MSCs (T-MSCs) showed abundant expression of immunomodulatory proteins, compared with MSCs derived from the bone marrow and adipose tissue [15,16]. Moreover, studies for T-MSCs described an immunomodulatory effect on degenerative or inflammatory diseases [17][18][19][20]. Our previous study also demonstrated an immunomodulatory effect of T-MSCs in a mouse model of allergic rhinitis [21].…”
Section: Introductionmentioning
confidence: 95%
“…Recently, palatine tonsil tissue was also identified as a source of MSCs and tonsil-derived MSCs (T-MSCs) showed abundant expression of immunomodulatory proteins, compared with MSCs derived from the bone marrow and adipose tissue [15,16]. Moreover, studies for T-MSCs described an immunomodulatory effect on degenerative or inflammatory diseases [17][18][19][20]. Our previous study also demonstrated an immunomodulatory effect of T-MSCs in a mouse model of allergic rhinitis [21].…”
Section: Introductionmentioning
confidence: 95%
“…It has been reported that the mortality rate is as high as 43% . According to an improved rat model, the mortality rate is 18.2%, due to anaesthetization for IR and asphyxia of teeth extraction. In the present study, we successfully created an ORN model in rats with improved survival rates up to 89% (16/18) by following modified modeling methods.…”
Section: Discussionmentioning
confidence: 99%
“…TMSCs have been tested in animal models of osteoporosis , osteoradinecrosis (ORN) , or calvarial defect and have demonstrated some promising outcomes as a feasible therapeutic treatment for bone‐related disorders (Table ). For example, tail injections of undifferentiated TMSCs or conditioned medium (CM) from TMSCs decreased the progression of osteoporosis in mice with BM depletion .…”
Section: Tonsil‐derived Mscs (Tmscs)mentioning
confidence: 99%
“…Similarly, the direct injection of undifferentiated TMSCs in proximal tibias of ovariecotmized (OVX) mice reduced the progression of osteoporosis . It is interesting to note that TMSCs themselves appear to have not only osteogenic but also wound healing properties even in the absence of induction from other osteogenic differentiation factors; the submucosal injection of undifferentiated TMSCs around the bone defect site decreased the risk of developing ORN caused by irradiation and tooth extraction in rats .…”
Section: Tonsil‐derived Mscs (Tmscs)mentioning
confidence: 99%